IMPROVING INTERPERSONAL INTELLIGENCE OF EARLY CHILDHOOD - Windisyah Putra; Asnawi (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
This study aimed to describe and know the implementation results of interpersonal intelligence development as well as to contribute positively for RA Bintang Zuhra Takengon Aceh Tengah, Aceh. This qualitative study was conducted by using psychological and sociological approaches. Data were collected through participatory observation, interviews, and documentations. Then, the data were analyzed through data reduction, data presentation, inference making, and data verification. The subjects in this study were 19 children of class B consisting of 12 girls and 7 boys in the even semester. Diverse activities were carried out by the children in order to develop their attitudes, habits, and understanding through playing while learning. The result of this study were: (1) the children’s interpersonal intelligence was developed through good samples, responsibilities, habits, courages, and disciplines; (2) the evaluation results showed that the percentage of the children’s intelligence reached 81.82%. This implied that the children’s interpersonal intelligence were in good level; (3) these results indicated the relevance between the improvement of interpersonal intelligence and the activities conducted in RKH. In conclusion, the children's interpersonal intelligence could be stimulated through playing with friends, collaboration, role plays, problems solving, and conflicts resolving.